0

# R2 plus 10r plus 25

Updated: 8/17/2019

Wiki User

14y ago

Best Answer

The quadratic expression: r2+10r+25 = (r+5)(r+5) when factorised

Wiki User

14y ago
This answer is:

## Add your answer:

Earn +20 pts
Q: R2 plus 10r plus 25
Write your answer...
Submit
Still have questions?
Related questions

(r + 5)(r + 5)

### LCM of r2-25 and r2 plus 14r plus 45?

The LCM is r^3 + 9r^2 - 25r - 225.

### Equation x2 plus Bx plus c equals 0 has 5 as the sum of its roots and 15 as the sum of the squares of its roots The value of 'c' is equals?

x2 - (-b/a)x + (c/a) = 0 or x2 - (sum of the roots)x + (product of the roots) = 0 Let the roots be r1 and r2. So we have: r1 + r2 = 5 (r1)2 + (r2)2 = 15 r1 = 5 - r2 (express r1 in term of r2) (5 - r2)2 + (r2)2 = 15 25 - 10r2 + (r2)2 + (r2)2 = 15 2(r2)2 - 10r + 25 = 15 (subtract 15 to both sides) 2(r2)2 - 10r + 10 = 0 (divide by 2 to both sides) (r2)2 - 5r + 5 = 0 (use the quadratic formula) r2 = [-b + &amp;- sq root of (b - 4ac)]/2a r2 = {-(-5) + &amp;- sq root of [(-5)2 - 4(1)(5)]}/2(1) = [5 + &amp;- sq root of (25 - 20)]/2 = (5 + &amp;- sq root of 5)/2 r1 = 5 - r2 r1 = 5 - (5 + &amp;- sq root of 5)/2 Thus, when r2 = (5 + sq.root of 5)/2, r1 = (5 - sq.root of 5)/2 or vice versa. Since the given equation is x2 + bx + c = 0, a = 1, then c equals to the product of roots. So that, c = (r1)(r2) = [(5 - sq.root of 5)/2][(5 + sq.root of 5)/2] = [52 - (sq.root of 5)2]/4 = 5

r2+r2 = 2r2

r+2

### WHAT IS R1 plus R2?

r1 plus r2 is the measurement of the combined electrical continuity of the phase conductor and circuit protective conductor on and electrical circuit.

### WHAT is r squared plus 9?

It could be lots of things. One answer can be: r2 + 9 = r2 + 32.

(pi*r2)/2 + 4000

(r + 2)(r + 2)

### What is r2 plus 6r-7 quadratically factorized?

r2+6r-7 = (r+7)(r-1) when factored

r -31

r(r + 5)